US Environmental Protection Agency's framework for human health risk assessment to inform decision making. (2017) - Fitzpatrick, Julie; Schoeny, Rita; Gallagher, Kathryn; Deener, Kathleen; Dockins, Chris; Firestone, Michael; Jordan, William; McDonough, Margaret; Murphy, Deirdre; Olsen, Marian; Raffaele, Kathleen
The US Environmental Protection Agency (EPA) has developed a framework for human health risk assessment to inform decision making. The National Research Council, in Science and Decisions, recommended that EPA adopt a framework for risk-based decision making, which maximises the utility of risk assessment. The framework considers the NRC's recommendations and builds upon existing agency guidance by emphasising the need to design risk assessments to provide information most applicable to the decision-making process. The framework ties together existing human health guidance, is flexible to accommodate the range of assessments conducted across the agency as well as future advances in risk assessment science, and considers overarching themes including environmental justice and susceptible lifestage risk. The framework integrates the concepts of planning and scoping and problem formulation and provides for incorporation of stakeholder involvement and peer review.